HIV self-tests for men who have sex with men, accessed via a digital vending machine: a qualitative study of acceptability. (April 2020) - Raffe, S; Pollard, A; Vera, JH; Soni, S; Peralta, C; Rodriguez, L; Dean, G; Llewellyn, CD
As the number of people living with undiagnosed HIV infection in the UK declines, innovative ways to access those least engaged with services are needed. This study explores the attitudes of men who have sex with men (MSM) towards using HIV self-testing (HIVST) kits distributed via a vending machine in a sauna (a licenced sex-on-premise venue). Twenty-three MSM attending the sauna were recruited to take part in semi-structured qualitative interviews. The participants were overwhelmingly positive about the HIVST vending machine. They identified convenience and flexibility as major benefits to testing in this way. The sauna was felt to be an appropriate location for the intervention. Limitations identified included the potential to reduce screening for other sexually transmitted infections and the inappropriate use of HIVST kits as a tool for risk-assessment prior to condomless sex, with a poor understanding of the window period. The implications of receiving a positive result without immediate access to support were also a concern. HIVST vending machines are an acceptable, innovative way to encourage HIV testing. Providers need to ensure this intervention is supported by adequate information regarding the limitations of the test and how to access comprehensive services to avoid any unintended negative effects.